2014
DOI: 10.1177/1049909114540318
|View full text |Cite
|
Sign up to set email alerts
|

Examining Forms of Spiritual Care Provided in the Advanced Cancer Setting

Abstract: Spiritual care (SC) is important to the care of seriously ill patients. Few studies have examined types of SC provided and their perceived impact. This study surveyed patients with advanced cancer (N = 75, response rate [RR] = 73%) and oncology nurses and physicians (N = 339, RR = 63%). Frequency and perceived impact of 8 SC types were assessed. Spiritual care is infrequently provided, with encouraging or affirming beliefs the most common type (20%). Spiritual history taking and chaplaincy referrals comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 17 publications
2
63
0
2
Order By: Relevance
“…(65) This indicates that there is a mismatch in perceptions regarding whether R/S discussion has taken place. Perhaps this confusion regarding what R/S discussion is, and when it is desired, leads to such discussions being offered less frequently.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(65) This indicates that there is a mismatch in perceptions regarding whether R/S discussion has taken place. Perhaps this confusion regarding what R/S discussion is, and when it is desired, leads to such discussions being offered less frequently.…”
Section: Discussionmentioning
confidence: 95%
“…(66-68)Doctor-initiated patient-doctor prayer was discussed in 15 studies. It was viewed positively by a range of 6.5-100% patients,(9,25,32,36,37,40,42,45,53,56,59,60,62,63,65) and 28-71% of patients thought it was appropriate for the doctor to pray for them at least some of the time (32,40,62,63). Prayer was more likely to be desired by those who were female, more religious or spiritual, of Roman Catholic faith, and/or facing more serious illness (37,40,63).…”
mentioning
confidence: 96%
“…Perhaps, this finding indicates that most patients and families are hesitant to ask their physicians to pray with them. One study by Epstein-Peterson et al 15 found that despite the inclusion of spiritual care in national palliative care guidelines, patients in the advanced cancer setting report that the actual provision of various types of spiritual care is nevertheless infrequent. In that study, for example, only 6% of patients and clinicians in this setting reported the provision of prayer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have pointed out that spiritual needs at the end of life often receive insufficient Spiritual care in hospice volunteers' training attention or remain entirely unnoticed (Hermann, 2007;Epstein-Peterson et al, 2014;Hampton et al, 2007;Vallurupalli et al, 2012). This is aggravated by the fact that people communicate their spiritual needs in a variety of ways.…”
Section: Spiritual Carementioning
confidence: 99%